1971
DOI: 10.1084/jem.133.4.713
|View full text |Cite|
|
Sign up to set email alerts
|

Studies on Antigen-Antibody Complexes

Abstract: In vivo-formed antigen-antibody complexes cause transient glomerulonephritis and vasculitis in experimental animals when appropriate antigens are administered to unimmunized animals in a single dose (1, 2). Similar antigens administered in multiple doses induce chronic disease (1, 3). Antigen, antibodies, and complement components have been demonstrated in lesions produced in this manner. Furthermore, antigen-antibody complexes have been shown as causative agents of glomerulonephritis in human systemic lupus e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

1973
1973
2009
2009

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 163 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…Circulating immune complexes cause inflammation of the vessel wall and accelerate atherosclerosis both in experimental animal models and in humans. Repeated injection of protein antigens leads to the formation of circulating immune complexes and to the acceleration of the spontaneous and diet-induced atherosclerotic process in both rabbits and mice (28,29). Premature atherosclerosis is also observed in patients with chronic immune complex formation due to inflammatory disorders (30,31), and there is an increased incidence of premature myocardial infarction in patients with systemic lupus erythematosus and autoimmune diseases characterized by circulating immune complexes (32).…”
Section: Discussionmentioning
confidence: 99%
“…Circulating immune complexes cause inflammation of the vessel wall and accelerate atherosclerosis both in experimental animal models and in humans. Repeated injection of protein antigens leads to the formation of circulating immune complexes and to the acceleration of the spontaneous and diet-induced atherosclerotic process in both rabbits and mice (28,29). Premature atherosclerosis is also observed in patients with chronic immune complex formation due to inflammatory disorders (30,31), and there is an increased incidence of premature myocardial infarction in patients with systemic lupus erythematosus and autoimmune diseases characterized by circulating immune complexes (32).…”
Section: Discussionmentioning
confidence: 99%
“…Kaetzel et al 13 have reported on active transport of immune complexes containing pIgA (pIgA-IC) across the epithelial cells by the same pIgR-dependent mechanism that normally applies to free pIgA. Several investigators [14][15][16][17][18] have emphasized the importance of the pIgR-dependent system for transport of pIgA-IC, rather than the mononuclear phagocyte system, which mediates a major clearance pathway of immune complexes in circulation. Thus, the decreased pIgR expression observed in ddY High mice may potentially not only result in serum pIgA elevation but also serum pIgA-IC accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…In order to explain the increased levels of circulating immune complexes in advanced liver diseases, two possibilities should be considered; increased formation and decreased hepatic clearance, that is, the disturbance of function of the reticuloendothelial system (Mannik et al 1971; Thomas et al 1978). The presence of serum Clq in higher concentrations might suggest the exemption of its consumption by binding with immune complexes in vivo, although immune complexes were detected by means of Clq radioimmunoassay.…”
Section: Discussionmentioning
confidence: 99%